Effects of induction docetaxel, platinum, and fluorouracil chemotherapy in patients with stage III or IVA/B nasopharyngeal cancer treated with concurrent chemoradiation therapy: Final results of 2 parallel phase 2 clinical trials. Issue 12 (13th February 2017) - Kong, Lin; Zhang, Youwang; Hu, Chaosu; Guo, Ye; Lu, Jiade J.
Abstract : BACKGROUND: The effects of docetaxel, platinum, and fluorouracil (TPF) induction chemotherapy plus concurrent chemoradiotherapy (CCRT) on locoregionally advanced nasopharyngeal cancer (NPC) are unclear. This study examined the long‐term outcomes of the addition of this regimen to CCRT for stage III and IVA/B NPC. METHODS: Two parallel, single‐arm phase 2 trials were performed synchronously to evaluate the efficacy and toxicity of TPF‐based induction chemotherapy in patients with stage III or IVA/B NPC. The induction chemotherapy, which preceded standard intensity‐modulated radiation therapy/platinum‐based chemoradiation, consisted of 3 cycles of docetaxel (75 mg/m 2 on day 1), cisplatin (75 mg/m 2 on day 1), and a continuous infusion of fluorouracil (500 mg/m 2 /d on days 1‐5) every 4 weeks. The primary endpoint for both trials was 5‐year overall survival (OS). RESULTS: Between January 2007 and July 2010, 52 eligible patients with stage III NPC and 64 eligible patients with nonmetastatic stage IV NPC were accrued to the 2 trials. With a median follow‐up of 67 months, the 5‐year OS, progression‐free survival, distant metastasis–free survival, and local progression‐free survival (LPFS) rates were all improved in comparison with historical benchmarks for patients with stage III or IVA/IVB NPC. Multivariate analyses indicated that T and N classifications (T1/T2 vs T3/T4 and N3 vs N0‐N2) were the only significant prognosticators for OS. The number of induction chemotherapy cycles was the only significant prognostic factor for predicting LPFS. CONCLUSIONS: TPF‐based induction chemotherapy appears to significantly improve outcomes in comparison with historical data when it is administered before CCRT for locoregionally advanced NPC. A phase 3 trial is currently being performed to confirm this benefit. Cancer 2017;123:2258–2267. © 2017 American Cancer Society . Abstract : Induction chemotherapy with docetaxel, platinum, and fluorouracil significantly improves the outcomes of patients with locally advanced nasopharyngeal cancer.